A linguistic account of singular terms - Polakof, Ana Clara (Aufklärung: journal of philosophy, 2021)
Vendler (1967b) discusses how we may linguistically recognize a singular term. Even though singular terms are relevant to Philosophy and not necessarily to Linguistics, it may be enriching to know what we can do to disambiguate such a term. Philosophically, singular terms are seen as singular definite descriptions which may be used to refer to a unique entity in the world. Vendler tried to provide a syntactic account of singular terms, and was not taken into account by philosophers. Linguistically speaking, a singular term will be a singular definite determiner phrase which may or may not correlate to something. We will show that a strictly syntactic account, as the one Vendler proposed, is deficient, and that it does not provide necessary and sufficient conditions to recognize a singular term. We will take into account Vendler’s spirit. We will use the advances in linguistics to explain how we may form a singular term, and provide syntactic-semantic conditions to recognize a singular term.